Case report: Cancer-free survival after chemotherapy, targeted immunotherapy combination with proton therapy following space making technique in a patient with cholangiocarcinoma after choledochal cyst resection - Kong, Jian; Xia, Qi; Xu, Li; Jin, Dongcun; Sun, Wenbing (Frontiers in Immunology, 2025)
Choledochal cysts (CCs) are rare cystic dilations of the intrahepatic and/or extrahepatic bile ducts. Malignancies arising during follow-up after excision of CCs have been reported in both children and adults, with no typical time frame for malignancy development. We present a case of a patient diagnosed with CCs 36 years ago, who underwent resection and subsequently developed cancer. The patient received chemotherapy, targeted therapy, and immunotherapy, with efficacy evaluation indicating a state of stable disease. Considering tumor resistance after continuous systemic therapy and an unresectable tumor, proton therapy was selected for the next treatment. To prevent gastrointestinal side effects after proton therapy, the bile-enteric anastomosis was dismantled, and a greater omentum strip was used to fill the subhepatic space, creating a barrier between the biliary duct and the intestine. The patient successfully underwent proton therapy without any gastrointestinal complications. As CC-associated malignancy poses a lifelong risk even with complete resection, surveillance should be maintained throughout the follow-up period. Comprehensive treatment should be adopted to improve prognosis in malignancy after CC resection.